FIGURE OF SPEECH ANALYSIS ON THREE POEMS OF JOHN DONNE - Dedi - Efendi (Universitas Muara Bungo, 2017)
Dedi Efendi, Figure of speech analysis on three poems of John Donne (Hymn to God my God, in my Sickness, A Hymn to God the Father and Death, be not Proud).The aim of this research is to find out the kinds of figure of speech and their meaning of figure of speech in three metaphysical poems. The writer analyzes the poems entitled Hymn to God my God, in my Sickness, A Hymn to God the Father and Death, be not Proud by John Donne.In this research, the writer uses qualitative research with descriptive analysis as the method of the research. He analyzes the poems by reading them intensively and giving attention to each line. After that, the writer tries to explicate the poems by examining the figure of speech and the biography of the poet.From the three poems, the writer has found eight types of figure of speech, they are: personification, metaphor, paradox, synecdoche, hyperbole, symbol, metonymy and apostrophe. The three poems have different theme, the first poem, Hymn to God my God, in my Sickness is a poem about preparation to face the death. The second poem, A Hymn to God the Father is a poem discussing about poet’s regret in his life. And the last poem Death, be not Proud is the most religious value. These poems discuss about considerably more positive about death and dying. Keywords: Figure of Speech Analysis on Three Poems